Antimicrobial Resistance of Aeromonas Species Isolated from Cultured Indian Major Carp, Labeo rohita: Possible Public Health Concern - Lavanya, Chethurajupalli; Neeraja, Tambireddy; Babu, P. Hari; Ramana, T. V.; Balasubramanian, A.; Meshram, Supradhnya; Sruthi, P. (International Journal of Bio-resource and Stress Management, 2021)
In India, Labeo rohita is widely cultured and consumed freshwater fish. Aeromonadsare etiological agents of major bacterial fish diseases like furunculosis, haemorrhagic septicaemia, skin ulcers, fin/tail rot and dropsy, causing significant economic losses in carp culture.Aeromonas species are widely distributed in aquatic environment which is considered as important vehicle of Aeromonas infections to fish and humans. Some of the Aeromonas spp. causes gastroenteritis, septicaemia, peritonitis, meningitis and eye infections in humans. In the present study Aeromonas species were isolated from diseased freshwater fish Labeo rohita collected from two districts viz., West Godavari and SPSR Nellore of Andhra Pradesh, India. A Total of 12 Aeromonas spp. were isolated and identified by biochemical tests. A. veronii bv. veronii (35%) was dominant when compared to other Aeromonas spp. Further, Antimicrobial resistance and multiple Antimicrobial resistance (MAR) of all Aeromonas spp. were tested against 17 antibiotics being frequently used for human diseases. The Antimicrobial resistance of all the 12 Aeromonas spp. have shown significantly high (p<0.05) resistance (100%) to ampicillin, amoxyclave and oxytetracycline except A. cavernicola when compared to other antibiotics. The MAR index of Aeromonas spp. ranged from 0.18-0.76, which indicates origination of isolated Aeromonas spp. from high risk sources of contamination. A. hydrophila, A. veronii bv. sobria, A. veronii bv. veronii, A. schubertii and A. jandaei isolated in this study were found to be pathogenic to humans also. The results revealed the pathogenic potential of Aeromonas infections in freshwater fish culture and emerging threats to public health.